Antioxidant, Antimicrobial and Spectroscopic Discussion of Guanine Azo Ligand with Cu(II) and Ag (I) Complexes - Edrees Fadhil, Asmaa; Khider Abbas, Alyaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In this paper, we have provided a very thorough analysis of a new novel chelate metal ion complex of [Cu(II),Ag(I)] prepared via the interaction with the ligand{ 2-amino-8-((4-chloro-3-hydroxyphenyl) diazenyl)azo]guanine} [LAAG], which is synthesized by diazo coupling of the 5-amino-2-chlorophenol with amino acid guanine. The ligand and its complexes are identified by a variety of techniques, like [HNMR, FTIR, and Uv-vis] spectral, thermal analysis (TGA), and element analyses (CHN). The molar ratio was achieved so that the Cu(II) complex has (1:2) (M:L) with octahedral geometry; however, the Ag(I) complex has (1:1) (M:L) with tetrahedral geometry, and the ligand acts as neutral N,N-bidentate; as well as the ligand (LAAG) and its complexes were assessed against the two types of bacteria (Klebsiella pneumonia, Staphylococcus aureus,antifungal (Candida), and antioxidant This study showed that all compounds (the ligand and its complexes) had antimicrobial activity and more biological activity.